Analisis Perbandingan Kualitas Pelayanan Richeese Factory Cabang Hasan Basri Kota Samarinda melalui Aplikasi Gojek dan Grab - Sabrina Emilia; Hairul Anwar (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to analyze the service quality comparison of Richeese Factory Hasan Basri Branch, Samarinda, based on customer reviews on Gojek and Grab applications from 2023 to 2024 using Pareto Diagram and Fishbone methods. A descriptive quantitative approach was employed using secondary data from customer reviews with ratings 1 to 4, reflecting service dissatisfaction. Complaints were categorized into mismatched orders, incomplete orders, and long preparation times, then analyzed to identify problem dominance for each application and year. The results indicate differences in primary problem categories between the two applications. In 2023, Gojek reviews were dominated by mismatched orders (58%), while Grab was dominated by incomplete orders (55%). In 2024, Gojek problems shifted to incomplete orders (50%), whereas Grab was dominated by mismatched orders (55%). Overall percentage change calculations show a significant increase in incomplete orders on Gojek by 93.93% and mismatched orders on Grab by 71.79%. Fishbone analysis identified causal factors such as inaccuracy in reading order notes, lack of completeness checks, inconsistent food quality, and inefficient preparation processes.